Applying media and virtual approaches to the institutionalization of Puzhou opera - Pang, Lin Lin; Loo, Fung Chiat; Chow, Ow Wei (Canadian Center of Science and Education, 2024)
Puzhou opera, also known as Puju, originated in Puzhou in ancient China, which is now renamed as Yuncheng city, Shanxi province. Puju has been recorded since the Yuan dynasty and has become one of China‘s most important operas because of its long history and influence on surrounding opera styles. This article explores challenges related to the institutionalization of Puju and how to use the modern technology of virtual media to ensure the sustainable development of traditional opera. In addition, as an insider of Yuncheng University, the researcher explored the application process of virtual media in promoting the institutionalized development of Puju and how to realize the learning, preservation, and inheritance of education and modern technology. To summarize, this study investigates the existing problems and challenges in using this virtual and media approaches and applies the media through virtual approach in the institutionalization of Puju to expand audiences and provide a new dissemination of opportunities.